Safe haven instruments – a comparison between the global financial crisis and the COVID-19 pandemic - Siemaszkiewicz, Karolina (Instrumenty safe haven – porównanie między globalnym kryzysem finansowym a pandemią COVID-19, 2021)
During the Global Financial Crisis (GFC) of 2008 and the COVID-19 pandemic, financial markets have e touched their lowest levels. This paper tried to compare the performance of safe haven assets during the Global Financial Crisis and the COVID-19 pandemic in such countries as Germany, Great Britain, France, Spain, Italy, and Poland. The author investigated the dynamic relations between gold, silver, the US Dollar Index, the Swiss Franc Index, soybean commodity futures and corn commodity futures. The study estimated the DCC or CCC models to compare the dynamic relation between the above-mentioned stock markets and financial instruments. The results showed that only gold could protect investors from stock market losses during both crises. During the GFC, gold, the USD Index, the Swiss Franc Index in almost all the considered countries could be identified as safe haven instruments. Surprisingly, the Swiss Franc Index acted as a safe haven instrument during the GFC but not during the COVID-19 pandemic.
Econometrics = Ekonometria, 2021, Vol. 25, No. 4, s. 1-16
Keywords: safe haven instruments; global financial crisis; COVID-19; pandemic; gold; dynamic correlation; instrumenty safe haven; globalny kryzys finansowy; pandemia; złoto; dynamiczna korelacja